RANCANGAN D-OPTIMAL UNTUK MODEL EKSPONENSIAL GENERAL - Tatik Widiharih; Sri Haryatmi; Gunardi Gunardi (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2014)
Exponential model is widely used in biology, chemistry, pharmacokinetics and microbiology. D-optimal criteria is criteria with the purpuse to minimize the variance of the estimator of parameters in the model. In this paper will discuss the D-optimal design for the generalized exponential model with homoscedastics errore assumtion. We used minimally supported design with the proportion of each design point is uniform. The optimization is used modified Newton, and the results obtained that the design points are interior points of the design region. Keywords: D-Optimal, Generalized Exponential, Minimally Supported Design, Support Point, Homoscedastics